Implementation of the Independent Law of Independent Campus Learning According to the Regulation of the Minister of Education and Culture No. 3 of 2020 concerning National Higher Education Standards - Saritua Silitonga; Siti Sundari; Annisa Danti Avrilia Ningrum (IHSA Institute, 2022)
Independent Learning The independent campus is a policy of the Minister of Education and Culture which aims to encourage students to master various sciences to enter the world of work. The Independent Learning Campus Policy implemented by the Minister of Education and Culture of the Republic of Indonesia is an innovative step that should be appreciated in an effort to improve quality human resources.The Minister of Education and Culture issued a policy for public and private universities to run the Independent Learning Campus by granting the right to study for 3 semesters outside the study program. This research will raise the problem, namely: how to apply the law of Merdeka Learning Merdeka Campus according to the Minister of Education and Culture No. 3 of 2020 concerning National Higher Education Standards. The research method used in this research is the normative legal method, which is a legal research obtained from a literature study by analyzing a legal regulation that is applied by an institution. The results of this study are: the Independent Learning Policy of the Independent Campus, providing opportunities for students to broaden their knowledge horizons,